Asymptomatic Localized Gastric Amyloidosis with Two Separate Lesions - Joo Hyun Lim; Jung Kim; Ji Yeon Seo; Jung Ho Bae (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Amyloidosis is a disease in which amyloid is abnormally accumulated in the tissue. The kidney and heart are the most commonly involved organs. Gastric involvement is relatively common in systemic disease; however, localized gastric amyloidosis is rare. Here, we report a case of localized gastric amyloidosis with two separate lesions. A 56-year-old woman underwent a health surveillance checkup without any noticeable symptoms. She was under medication for diabetes and dyslipidemia, and was otherwise healthy. On surveillance upper endoscopy, an irregularly shaped hyperemic elevated erosion at the gastric fundus and a 1.5-cm, yellowish subepithelial tumor-like lesion with intact overlying mucosa at the lesser curvature of the lower body of the stomach were detected. Endoscopic biopsy revealed submucosal eosinophilic material deposition in both lesions. Congo-red staining showed amyloid deposit appearing as a yellow-green birefringence under polarizing microscopy. Echocardiography, abdominal sonography, and colonoscopy revealed no abnormality. The patient was diagnosed as having localized gastric amyloidosis and is now undergoing regular follow-up without any treatment. Localized gastric amyloidosis is a rare disease that may mimic nonspecific gastritis or subepithelial tumor. However, endoscopic biopsy with appropriate staining may be diagnostic and thorough evaluation for systemic involvement is important.